Secondary Education in Extremadura through its students. The Provincial Historical Institutes of Cáceres and Badajoz (1900-1936) - Redondo Castro, Cristina; Grana Gil, Isabel (Historia y Memoria de la Educación, 2022)
The first third of the 20th century was a period of great social and cultural transformations. But how did these changes affect secondary education in Extremadura? The objective of this article is to analyze the development and evolution of secondary education (official, collegiate and free) in Extremadura in the years between 1900 and 1936 through the tracing of students enrolled in the historical institutes of Caceres and Badajoz. To do so, in this work we have not only resorted to quantitative analysis through tables and graphs that show data on the enrolled population, including their origin, types of education, differences by sex, etc., but we have focused on detecting the causes that influenced the evolution, or lack thereof, of this educational level. We conclude that, although the process of democratization of this type of education began thanks to educational policies enacted during the first third of the 20th century, especially during the Second Republic - favored by the implantation of new schools as well as to the fact that a degree was required to become a teacher – the overall impact was limited in Extremadura. This owes to a combination of a high rate of illiteracy in the area, a scattered population and low economic development, among other causes